Heteroatom‐Doping of Non‐Noble Metal‐Based Catalysts for Electrocatalytic Hydrogen Evolution: An Electronic Structure Tuning Strategy. Issue 4 (25th January 2021) - Wang, Jing; Liao, Ting; Wei, Zhongzhe; Sun, Junting; Guo, Junjie; Sun, Ziqi
Abstract: Electrocatalytic water splitting for hydrogen production is an appealing way to reduce carbon emissions and generate renewable fuels. This promising process, however, is limited by its sluggish reaction kinetics and high‐cost catalysts. Construction of low‐cost and high‐performance non‐noble metal‐based catalysts have been one of the most effective approaches to address these grand challenges. Notably, the electronic structure tuning strategy, which could subtly tailor the electronic states, band structures, and adsorption ability of the catalysts, has become a pivotal way to further enhance the electrochemical water splitting reactions based on non‐noble metal‐based catalysts. Particularly, heteroatom‐doping plays an effective role in regulating the electronic structure and optimizing the intrinsic activity of the catalysts. Nevertheless, the reaction kinetics, and in particular, the functional mechanisms of the hetero‐dopants in catalysts yet remains ambiguous. Herein, the recent progress is comprehensively reviewed in heteroatom doped non‐noble metal‐based electrocatalysts for hydrogen evolution reaction, particularly focus on the electronic tuning effect of hetero‐dopants in the catalysts and the corresponding synthetic pathway, catalytic performance, and activity origin. This review also attempts to establish an intrinsic correlation between the localized electronic structures and the catalytic properties, so as to provide a good reference for developing advanced low‐cost catalysts. Abstract : This review systematically illuminates the doping effect on regulating the electronic structure of the non‐noble metal‐based catalysts toward hydrogen evolution reaction, and primarily establishes the relationships between doping structure and catalytic performance, and further provides a valuable guidance for the researchers on the doped elements selection and their activity study.